RUSSIAN NATIONAL PEDIATRIC MEDICATION GUIDELINES (FORMULATION) AND MEDICATION INFORMATIONAL RESOURSES - A.A. Baranov; V.K. Tatochenko; L.S. Namazova; G.A. Samsygina; K.I. Saitkulov (Педиатрическая фармакология)
.